Who Is the Muslim? Discursive Representations of the Muslims and Islam in Indian Prime-Time News - Drabu, Onaiza (Religions, 2018)
A cursory look at Indian prime-time news tells us much about the tone and tenor of the people associated with it. Exaggerations, hyperbole, and tempers run wild, and news anchors flail in theatrical rage. News channels and news editors display their ideological affiliations subliminally. These affiliationsa factor of personal political stances, funding bodies, and investorslead to partisan bias in the framing of news and, in some cases, can easily translate into racial prejudice. In this paper, I examine news coverage related to Muslims in India. I study the coverage of two issues specificallylove jihad and triple talaqin prime-time English news of two channels: Times Now and Republic TV. Love jihad is a term used to describe alleged campaigns carried out by Muslim men targeting non-Muslim women for conversion to Islam by feigning love. Triple talaq is a form of divorce that has been interpreted to allow Muslim men to legally divorce their wives by stating the word talaq three times. My analysis of the content, tone, and tenor of their coverage shows that these channels propagate associations between Islam and backwardness, ignorance, and violence through consistent employment of the following tropes: Muslim women need to be saved from Muslim men; Hindu women need to be saved from Muslim men; and, Muslims are not fully Indianthey are anti-national. I place this study of news media within the current political climate in India and briefly touch on the conversations it guides and provokes. This is a first step in detailing a problem. It is also a call for further analysis on this subject to examine and evaluate if and how discourse manipulates public conversations and policy decisions.